Commissioning social care for people with dementia living at home: Findings from a national survey. (10th November 2019) - Davies, Sue; Hughes, Jane; Ahmed, Saima; Clarkson, Paul; Challis, David; ,
Abstract : Objective: To explore the complexities, circumstances, and range of services commissioned for people with dementia living at home. Methods: A national survey was used to collect data from English local authorities in 2015. Commissioners of services for older adults were invited to complete a questionnaire. An exploratory cluster analysis of nominal data was conducted using a TwoStep procedure to identify distinct groups. Results: A total of 122 authorities (83%) responded to the request. Four approaches to commissioning were identified, reflecting commissioning practices at the organisational, strategic, and individual service user levels. Commissioning at the service user level was most apparent. Bivariate analysis found that these configurations were not associated with the types of dementia specific services provided but were related to the number available. Authorities delivered a greater range of specialist services when joint commissioning between social care and health partners was undertaken. However, the joint commissioning of services was less observed in services specifically for people with dementia than in generic services for all older people. There was limited evidence that local circumstances (population configuration and deprivation levels) were associated with this approach to commissioning. Conclusions: The significant role of health partners in the delivery of social care services to support older people living with dementia in their own homes is evident. As the population with dementia ages and physical health needs increase, how dementia specific services differ from and complement those services available to all older people warrants further investigation.